# Simplify. Remove grouping symbols and combine like terms. A) `2[5(x+y)-2(3x-4y)]` B) `6x-3(x-2y)`

### 1 Answer | Add Yours

(A)

To simplify expressions with nested parenthesis, start at the innermost expression.

Remove the parenthesis inside the bracket. To do so, distribute 5 to x+y and -2 to 3x-4y.

`=2[5x+5y-6x+8y]`

Combine like terms.

`=2[-x+13y]`

`=2[13y-x]`

And distribute 2 to 13y-x.

`=26y - 2x`

**Hence, `2[5(x+y)-2(3x-4y)]=26y-2x` .**

(B)

`6x-3(x-2y)`

To simplify, remove the parenthesis by distributing -3 to x-2y.

`=6x-3x+6y`

And, combine like terms.

`=3x+6y`

**Hence, `6x-3(x-2y)=3x+6y` .**